Physical metallurgy - Cahn, R. W. (Robert W.), 1924-2007.; Haasen, P. (Peter) (Amsterdam ; New York : North-Holland, 1996)
This is the fourth edition of a work which first appeared in 1965. The first edition had approximately one thousand pages in a single volume. This latest volume has almost three thousand pages in 3 volumes which is a fair measure of the pace at which the discipline of physical metallurgy has grown in the intervening 30 years. Almost all the topics previously treated are still in evidence in this version which is approximately 50% bigger than the previous edition. All the chapters have been either totally rewritten by new authors or thoroughly revised and expanded, either by the third-edition authors alone or jointly with new co-authors. Three chapters on new topics have been added, dealing with dry corrosion, oxidation and protection of metal surfaces; the dislocation theory of the mechanical behavior of intermetallic compounds; and (most novel) a chapter on polymer science for metallurgists, which analyses the conceptual mismatch between metallurgists' and polymer scientists' way of looking at materials. Special care has been taken throughout all chapters to incorporate the latest experimental research results and theoretical insights. Several thousand citations to the research and review literature are included in this edition. There is a very detailed subject index, as well as a comprehensive author index. The original version of this book has long been regarded as the standard text in physical metallurgy and this thoroughly rewritten and updated version will retain this status.
v. 1. Crystal structure of the metallic elements. Electron theory of metals. Structure and stability of alloys. Structure of intermetallic compounds and phases. Metallurgical thermodynamics. Phase diagrams. Diffusion in metals and alloys. Solidification. Microstructure -- v. 2. Qualitative and quantitative surface microscopy. Transmission electron microscopy. X-ray and neutron scattering. Interfacial and surface microchemistry. Oxidation, hot corrosion and protection of metallic materials. Diffusive phase transformations in the solid state. Phase transformations, nondiffusive. Physical metallurgy of steels. Point defects. Metastable states of alloys -- v. 3. Dislocations. Mechanical properties of single-phase crystalline media: deformation at low temperatures. Mechanical properties of single-phase crystalline media: deformation in the presence of diffusion. Mechanical properties of solid solutions. Mechanical properties of intermetallic compounds. Mechanical properties of multiphase alloys. Fracture. Fatigue. Recovery and recrystallization. Magnetic properties of metals and alloys. Metallic composite materials. Sintering processes. A metallurgists guide to polymers.
Includes bibliographical references and indexes.
Keywords: Physical metallurgy; Engineering; Mining engineering; Electronic books